Economic evaluation of the application of intelligent metal processing technologies for reducing enterprise operating costs - Kolosov, Artem (Актуальні питання економічних наук, 2026)
The relevance of the study is determined by the increasing requirements for the efficiency of industrial enterprises under conditions of resource constraints and external instability caused by Russia’s aggression against Ukraine. In this context, the intellectualization of metal processing is considered a key direction for reducing operating costs and improving the controllability of production systems. At the same time, the lack of a coherent economic evaluation framework limits the scalability of such technologies. The purpose of the article is to substantiate the theoretical and methodological foundations for the economic evaluation of the application of intelligent metal processing technologies in the context of reducing operating costs of industrial enterprises. Methods. The study employs methods of system analysis, generalization and systematization of scientific approaches, comparative analysis, as well as analytical methods for assessing the economic efficiency of production processes. Results. The economic essence of intelligent metal processing technologies and their role in transforming production management have been investigated. The mechanisms of influence of intellectualization on the structure of operating costs have been identified, including optimization of processing modes, reduction of defects, improved equipment utilization, and rationalization of energy consumption. Approaches to the economic evaluation of implementation efficiency have been generalized based on the integration of investment, cost, and performance indicators. It has been proven that the economic effect is systemic and delayed in nature, which requires a comprehensive evaluation approach. The main challenges have been identified, including variability of production conditions, data fragmentation, difficulties in measuring intangible effects, and the gap between operational and financial indicators. Conclusions. It has been proven that improving the efficiency of intelligent technologies requires their phased integration into production processes, the formation of a unified digital environment, and the implementation of continuous monitoring systems for economic results. Further research should focus on the development of quantitative models for evaluating delayed economic effects, improvement of methods for measuring intangible outcomes of intellectualization, and integration of operational and financial indicators into comprehensive analytical management systems.